Bean growth and yield as affected by depth of phosphate fertilizer application - Chaib, Sérgio L.; Bulisani, Eduardo A.; Castro, Lucia Helena S. M. (Pesquisa Agropecuaria Brasileira, 2014)
Several depths (0, 5, 10, 15, 20, 25 and 30 cm) of fertilizer application were studied to observe the growth and development of roots and aerial parts of bean plants (Phaseolus vulgaris L.) in a clayey texture Purple Latosol (Haplortox). Aerial parts were enhanced by fertilizer placed from 10 to 25 cm of depth. Grain yield, however, was equal in all of the treatments, due to an adequate water supply even in the dry season. Toot weight, which was evaluated in greenhouse in PVC tubes with openings each 5 cm up to 30 cm, was influenced by the fertilizer, being increased in those layers where it was applied.
Keywords: Phaseolus vulgaris L.; roots; aerial parts; grains; soils